Fire history influences large‐herbivore behavior at circadian, seasonal, and successional scales. Issue 8 (1st October 2018) - Spitz, Derek B.; Clark, Darren A.; Wisdom, Michael J.; Rowland, Mary M.; Johnson, Bruce K.; Long, Ryan A.; Levi, Taal
Abstract: Recurrent environmental changes often prompt animals to alter their behavior leading to predictable patterns across a range of temporal scales. The nested nature of circadian and seasonal behavior complicates tests for effects of rarer disturbance events like fire. Fire can dramatically alter plant community structure, with important knock‐on effects at higher trophic levels, but the strength and timing of fire's effects on herbivores remain unclear. We combined prescribed fire treatments with fine‐scale location data to quantify herbivore responses to fire across three temporal scales. Between 2001 and 2003, 26 stands of fir ( Abies spp.) and Douglas‐fir ( Pseudotsuga menziesii ) were thinned and burned; 27 similar stands were left untreated as experimental controls. Analyzing female elk ( Cervus canadensis ) locations across 21 yr (1996—2016), we found crepuscular, seasonal, and successional shifts in behavioral responses to fire. Elk displayed "commuting" behavior, avoiding burns during the day, but selecting them at night. Elk selection for burns was strongest in early summer and the relative probability of elk using burns peaked quickly (5 yr post burn) before gradually returning to pre‐treatment levels (15 yr post burn). Our results demonstrate that fire history has complex, persistent effects on herbivore behavior, and suggest that herbivores benefit from heterogeneous landscapes containing a range of successional stages.